Gestión financiera de la pymes y sus efectos en el desarrollo socio económico del área comercial del cantón Santo Domingo, año 2013 instructivo de inserción. - Guerra Herrera, Kleber Santos (2015)
In the commercial area of the Santo Domingo city, small and medium enterprises (SMES) specially dedicated to the commercialization of products, services and manufacturing, which cater, the different needs of the local market, thus must realize a financial management planned manner to achieve suitable management of resources, as applying techniques that allow them to view financial strategies for attaining higher profitability and lower costs that incur to discharge with outing of business which are engaged in the local market. Local microenterprises execute an important role in the interests of development as they are an active part of the local economy, it is, they satisfy local needs for goods and services, generate significant employment opportunities actively contribute in tax matters, factors that justify why their presence in the local environment, which make them then generator engine of growth and development for the canton. therefore, it is necessary to design a proposal that would allow small and medium enterprises join and benefit from the advantages that contemplate the National Plan for Good living for benefit of the microenterprise sector ,for that management tools are designed, tax management and financial assessment allows them to benefit from those contemplated within the productive matrix which today is implemented in the country, as designed new model of planning and development of the current government